Clusters of spreading depolarizations are associated with disturbed cerebral metabolism in patients with aneurysmal subarachnoid hemorrhage - Sakowitz, Oliver; Santos, Edgar; Krajewski, Kara Leigh; Hertle, Daniel; Vajkoczy, Peter; Unterberg, Andreas (Stroke, 2013)
Background and Purpose—We studied the dynamics of extracellular brain tissue concentrations of glucose, lactate, pyruvate, and glutamate during the occurrence of spreading depolarizations (SDs) in patients with aneurysmal subarachnoid hemorrhage. Methods—In this prospective observational study, patients with aneurysmal subarachnoid hemorrhage received multimodal cerebral monitoring, including intracranial pressure, cerebral microdialysis, and subdural electrocorticography. Results—Seven of the 17 recruited patients had intracerebral hemorrhage, acute ischemia and severe brain oedema leading to acute ischemic neurological deficits associated with early disturbance of metabolism at the recording site. They displayed a total of 130 SDs. The remaining 10 patients without acute ischemic neurological deficits exhibited 138 single SDs and 68 SDs in clusters. In patients without acute ischemic neurological deficits, clustered SDs were associated with a significant transient decrease in glucose and increase in lactate compared with baseline during the first 140 minutes after SDs. Moreover, the number of clustered SDs correlated with the outcome (R=−0.659; P<0.01). Conclusion—SDs can propagate in nonischemic human brain tissue. Clusters of SDs are related to metabolic changes suggestive of ongoing secondary damage in primarily nonischemic brain tissue.